Percutaneous left atrial decompression in adults with refractory cardiogenic shock supported with veno‐arterial extracorporeal membrane oxygenation. Issue 6 (11th May 2017) - Alhussein, Mosaad; Osten, Mark; Horlick, Eric; Ross, Heather; Fan, Eddy; Rao, Vivek; Billia, Filio
Abstract: Background and Aim of the Study: Left ventricular (LV) distention, a recognized complication in patients supported with veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) for refractory cardiogenic shock, can lead to pulmonary edema, increased myocardial oxygen consumption, and LV thrombus formation. Atrial septostomy was examined as a management strategy for LV distension. Methods: Of 72 patients supported with VA‐ECMO, seven patients underwent atrial septostomy through a trans‐septal approach. The primary indication for atrial septostomy was refractory pulmonary edema. Results: The mean time from ECMO initiation to LA decompression was 1.3 days (range 0‐2 days). There was a 100% procedural success rate with improvement in pulmonary edema. Five patients survived to discharge with one patient exhibiting recovery of biventricular function, two patients were transplanted, one patient was decannulated, and one patient was transitioned to long‐term durable ventricular assist device. Two patients died, one from multi‐organ failure and one with severe anoxic brain injury. Conclusion: Atrial septostomy is an effective method of LV decompression that can be performed safely with a high success rate.